Prevalência de hipovitaminose D em idosos institucionalizados em Passo Fundo/RS - Paiva, Cezar Augusto Caleffi (2011)
We conducted cross-sectional, prospective study with probability sampling, in the institutionalized elderly population of the city of Passo Fundo, RS, in order to estimate the prevalence of hypovitaminosis D (25 (OH) D below 30 ng / mL). Of a total of 305 elderly, measured the levels of 25-hydroxyvitamin D of 77 subjects, correlating them with socioeconomic and demographic data, medications, comorbidities, daily habits and laboratory tests. Subsequently, subjects were divided according to levels of vitamin D forming a group with severe hypovitaminosis D (25 (OH) D below 10 ng / mL) and another group with deficiency, insufficiency and sufficiency (equal or greater than 10 ng / mL) to identify possible factors associated with the first. The results showed high prevalence of hypovitaminosis D (97%), especially of severe intensity (64.9%). The marked deficiency of vitamin D was only associated with albumin levels (p = 0.048), whereas those with severe hypovitaminosis had a mean serum albumin 3.5 g / dL (± 0.1) and the remaining of 3.7 g / dL (± 0.4). There was also an association between severe hypovitaminosis D and walking with restrictions, but without statistical significance (p = 0.083). The elderly who walk with restrictions, 21 (77.8%) had severe deficiency and those who walk without restrictions, 29 (58.0%) had it. It was clear, though, a negative correlation between serum levels of 25 (OH) D and PTH (rs = -0,24, p=0,033), and secondary hyperparathyroidism occurred in 32.5% of elderly in the sample. In conclusion, it appears that there is high prevalence of hypovitaminosis D, including severe in the elderly institutionalized in focus in this study. Therefore, it is necessary to educate health professionals and caregivers about the need for interdisciplinary measures to minimize the problem